Kainate and AMPA receptors in epilepsy: Cell biology, signalling pathways and possible crosstalk. (1st September 2021) - Henley, Jeremy M.; Nair, Jithin D.; Seager, Richard; Yucel, Busra P.; Woodhall, Gavin; Henley, Benjamin S.; Talandyte, Karolina; Needs, Hope I.; Wilkinson, Kevin A.
Abstract: Epilepsy is caused when rhythmic neuronal network activity escapes normal control mechanisms, resulting in seizures. There is an extensive and growing body of evidence that the onset and maintenance of epilepsy involves alterations in the trafficking, synaptic surface expression and signalling of kainate and AMPA receptors (KARs and AMPARs). The KAR subunit GluK2 and AMPAR subunit GluA2 are key determinants of the properties of their respective assembled receptors. Both subunits are subject to extensive protein interactions, RNA editing and post-translational modifications. In this review we focus on the cell biology of GluK2-containing KARs and GluA2-containing AMPARs and outline how their regulation and dysregulation is implicated in, and affected by, seizure activity. Further, we discuss role of KARs in regulating AMPAR surface expression and plasticity, and the relevance of this to epilepsy. This article is part of the special issue on 'Glutamate Receptors - Kainate receptors'. Highlights: Brief overview of cell biology of AMPARs and KARs. Evidence for AMPAR and KAR involvement in in animal models and human epilepsy. Potential roles for ADAR2 mRNA editing of GluA2 and/or GluK2 in epilepsy. Interplay between KARs and AMPARs and implications for epilepsy. Possible future directions.